Approximation by mean of the function given by dirichlet series by absolutely convergent Dirichlet series - Laurinčikas, A. (Nonlinear Analysis: Modelling and Control, 1998)
It is proved an uniform on compact sets approximation by mean of the general Dirichlet series.
Keywords: none